SOUND RADIATION ANALYSIS OF LOW ORDER VIBRATION MODES FROM A FINITE CYLINDRICAL SHELL IN DIFFERENT FLUIDS - DONG KangJun; FENG Yang (Jixie qiangdu)
By means of Green’s function and modal expansion technique,the coupled vibration and sound equation of the finite cylindrical shells are investigated based on the flugge theory of the shells. The expression of the sound radiation and the radial quadratic velocity are solved. And then,the contributions of the low order vibration modes to the sound radiation and the radial quadratic velocity are also discussed in different fluids. The results show that more vibration modes contribute to the sound power of the finite cylindrical shells in air,however,the influence of the fluid-structure coupling on the radial squared velocity of the shells is very remarkable in water,the performance of the sound power radiated from the finite cylindrical shells is decreased with the increase of the circumferential vibration modes,and only first several vibration modes are required to accurately calculate the sound power.